Portable X‐Ray Fluorescence Spectroscopy as a Tool for Cyclostratigraphy. (21st May 2019) - Saker‐Clark, Matthew; Kemp, David B.; Coe, Angela L.
Abstract: Cyclostratigraphic studies are used to create relative and high‐resolution time scales for sedimentary successions based on identification of regular cycles in climate proxy data. This method typically requires the construction of long, high‐resolution data sets. In this study, we have demonstrated the efficacy of portable X‐ray fluorescence spectroscopy (pXRF) as a nondestructive method of generating compositional data for cyclostratigraphy. The rapidity (100 samples per day) and low cost of pXRF measurements provide advantages over relatively time‐consuming and costly elemental and stable isotopic measurements that are commonly used for cyclostratigraphy. The nondestructive nature of pXRF also allows other geochemical analyses on the same samples. We present an optimized protocol for pXRF elemental concentration measurement in powdered rocks. The efficacy of this protocol for cyclostratigraphy is demonstrated through analysis of 360 Toarcian mudrock samples from North Yorkshire, UK, that were previously shown to exhibit astronomical forcing of [CaCO3 ], [S], and δ 13 Corg . Our study is the first to statistically compare the cyclostratigraphic results of pXRF analysis with more established combustion analysis. There are strong linear correlations of pXRF [Ca] with dry combustion elemental analyzer [CaCO3 ] ( r 2  = 0.7616) and of pXRF [S] and [Fe] with dry combustion elemental analyzer [S] ( r 2  = 0.9632 and r 2  = 0.9274, respectively). Spectral and cross‐spectral analyses demonstrate that cyclicity previously recognized in [S], significant above the 99.99% confidence level, is present above the 99.92% and 99.99% confidence levels in pXRF [S] and [Fe] data, respectively. Cyclicity present in [CaCO3 ] data above the 99.96% confidence level is also present in pXRF [Ca] above the 98.12% confidence level. Plain Language Summary: As the Earth rotates around the Sun, its orbit subtly changes over tens of thousands of years, and this controls Earth's climate. Earth's climate, in turn, influences the amount and type of sediment that gets deposited. These orbital changes can be recognized in sedimentary rocks as cyclic variations in chemistry. The cycles can be used to calculate how long it took to deposit sediments and are known as cyclostratigraphy. To recognize and measure cycles in the rock record typically requires hundreds of expensive and time‐consuming analyses. In this study we improved a method of analyzing the chemistry of rocks using a portable X‐ray fluorescence instrument. We used 360 samples of mudrock to statistically compare our new method using the portable X‐ray instrument with the results determined previously by more time‐consuming and more expensive combustion methods. Our study has shown for the first time that the cyclostratigraphy data produced using this portable X‐ray tool are mathematically indistinguishable from these conventional chemical methods. This study is important because it shows that it is possible to more cheaply and efficiently construct robust cyclostratigraphic time scales using the X‐ray instrument. Such cyclostratigraphic time scales can be used to understand the rate of Earth processes such as climate change and evolution of organisms. Key Points: Optimized portable X‐ray fluorescence spectroscopy method allows fast and nondestructive production of elemental data from mudrock powders Analysis of portable X‐ray fluorescence spectroscopy and combustion analysis data yield spectral peaks of similar statistical significance Portable X‐ray fluorescence spectroscopy is suitable for producing cyclostratigraphic time series for identifying orbital forcing